Adoption and Diffusion of Solar Products in Indore: A Study on Barriers for Non-Adoption of Solar Energy Systems in Domestic Households - Nag, Archana; Chowdhary, Rupal (Prabandhan: Indian Journal of Management, 2019)
An ever increasing consciousness towards sustainable development and environmental conservation has laid an emphasis on replacing conventional energy sources by renewable energy systems. In line with Clean and Green India movement, a study was conducted among individual households/owners in Indore, Madhya Pradesh which was aimed at identifying the adoption and diffusion of solar products like solar inverters, solar water heating systems, and solar lights to name a few. The study mainly focused on the barriers in adoption of solar energy and also the perceptions of domestic users about solar energy products were studied on the basis of variables like cost, awareness among people about various governmental initiatives, environmental awareness, relative advantage of using solar power over conventional energy sources, etc. The findings of the study revealed that though people were environmentally conscious and were aware about the advantages of using solar products but the perceived high costs, financial constraints, lack of awareness about governmental initiatives, and lack of promotional activities were some of the major barriers which led to non-adoption of solar products as a renewable energy source. The findings may help in predicting the purchase patterns of individual customers for solar products, and thereby in designing marketing strategies, creating awareness about solar products, and increasing the use of renewable energy sources among individual households.